Removal of Gutta-Percha/Zinc-Oxide-Eugenol Sealer or Gutta-Percha/Epoxy Resin Sealer from Severely Curved Canals: An In Vitro Study - Santhoshini Reddy; Prasanna Neelakantan; Mohammad Ali Saghiri; Mehrdad Lotfi; Chandragiri Venkata Subbarao; Franklin Garcia-Godoy; James L. Gutmann (Hindawi Limited, 2011)
The aim of this study was to compare the cleanliness of root canal walls after retreatment using two rotary retreatment files to hand instruments in severely curved canals obturated with gutta-percha and two different sealers. Single rooted mandibular premolars (n=90) with root curvatures were instrumented and obturated with gutta-percha and an epoxy resin (Group 1, n=45) or zinc oxide eugenol sealer (Group 2, n=45). Following retreatment of the specimens (n=15 ProTaper Universal Retreatment Files (Subgroup B) or R-Endo retreatment files (Subgroup C) after 1 month, split specimens were examined under a stereomicroscope and the percentage of remaining root filling material was statistically compared using one way ANOVA with Bonferroni adjustment for multiple comparisons (P=0.05). The R-Endo system performed significantly better than the other two file systems (P<0.05). None of the systems used in this study cleaned root canals thoroughly. The R-Endo system did provide cleaner walls when compared to the other instruments used. The type of root filling materials had an impact on the outcomes with all techniques.